Prevalence of dental trauma in permanent anterior teeth in 6-12-year-old children in school going children of East Delhi - Khandelwal, Deepak; Kalra, Namita; Tyagi, Rishi; Khatri, Amit; Yangdol, Padma (International Journal of Contemporary Pediatrics, 2023)
Background: Traumatic dental injury affects many children and adolescents, and it considered a challenging public health problem. Injuries involving permanent teeth are one of the most common types of trauma to the maxillofacial area. The prevalence of traumatic dental injuries varies greatly, and it ranges from 4% to 58% Methods: A cross-sectional survey was carried among 700 school children aged 6 and 12 years in East Delhi. A list of primary and secondary schools of East Delhi area was obtained. A multistage random sampling technique was adopted to select the study population. The children aged 6-12 years with signed consent and in whom permanent anteriors had erupted were included in the study. The oral examination was conducted by a single calibrated examiner using WHO oral health assessment Performa 2013. Results: Overall prevalence was 7.71%. Dental trauma was 1.90%, 10.27% and 10.12% respectively in Group I, Group II and Group III respectively. Female reported with 7.57 % and males with 10.81% (p=0.001). Maxillary Central incisors were found to be the most frequent teeth to be injured. Conclusions: Parents may lack information regarding the consequences of dental trauma and don’t report for dental consultation. Along with seeking dental care, patient must be educated about the use of protective mouth guards while playing contact sports which may help to reduce the incidence and severity of dental injuries.